O patrimônio cultural e a legislação municipal: estudo de caso de Ribeirão Preto (SP) - Lucatelli, Luis Gustavo (Universidade Federal de São Carlos, 2025)
This study takes the urban functions of Ribeirão Preto (São Paulo, Brazil) as its backdrop, analyzed through the interaction between two of its structuring elements: municipal legislation and cultural heritage. Legal norms, expressed through laws and decrees, serve to define and regulate cities, as well as to protect cultural heritage, whose concept is not static but rather a constantly evolving field, shaped by symbolic, political, and economic disputes. These tensions reflect urban and social dynamics, highlighting cultural heritage as a space of negotiation between collective memory and territorial transformation interests. The aim of this research is, therefore, to understand how municipal legislation has been applied in the protection of cultural heritage in the city, through a case study. To this end, regulations from the three levels of government were examined, with particular attention to local legislation, and officially protected built heritage assets were systematized. The relevance of this study lies in understanding how municipal law can serve as a tool for the preservation and valorization of cultural heritage amid processes of urban transformation. By investigating how municipal legislation incorporates cultural heritage, the research contributes to academic and technical discussions by offering reflections on policy-making in local contexts—emphasizing, in this way, the importance of urban planning integrated with cultural preservation. The methodology adopted combined three approaches: a literature review on cultural heritage, urbanism, and public policy; documentary analysis of federal, state, and municipal legislation of Ribeirão Preto, with the latter organized according to administrative periods up to 2025; and a survey based on data from CONPPAC-RP. Consultations were also conducted with agents involved in heritage management, expanding the understanding of the concrete application of political instruments. Finally, the protected assets were georeferenced using QGIS, enabling the visualization of how these policies are territorially distributed. The results point to progress in protection actions, with growing recognition of both tangible and intangible heritage and the incorporation of guidelines from the 1988 Constitution and the City Statute. However, challenges remain, such as institutional fragmentation, weak coordination among involved agencies, and limited public participation. These factors undermine the effectiveness of preservation policies. The study concludes that an integrated approach—sensitive to local specificities and focused on valuing urban memory—is essential to strengthening heritage protection in the face of development dynamics.
Cultural heritage and municipal polices: a case study of Ribeirão Preto (SP)
Keywords: Patrimônio cultural; Instrumento urbano; Planejamento urbano; Ribeirão Preto; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL